FORMULASI PENGATURAN PENANGGUHAN PENAHANAN DENGAN JAMINAN UANG OLEH KEPOLISIAN, KEJAKSAAN, DAN HAKIM DALAM HUKUM ACARA PIDANA DI INDONESIA - Simamora, Erwin Hariadi; Indra, Mexsasai; Erdiansyah, Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Article 31 Paragraph 1 (One) of Law Number 8 of 1981 concerning the Criminal Procedure Code states that at the request of a suspect or defendant, investigators, public prosecutors and judges, in accordance with their respective authorities, may hold a suspension of detention with or without a guarantee of money. The implementation of the suspension of detention with a guarantee of money is regulated in Article 35 Paragraph 1 (One) Government Regulation Number 92 Year 2015 Regarding the Second Amendment to Government Regulation Number 27 Year 1983 Regarding the Implementation of the Criminal Procedure Code does not regulate the amount of the detention suspension and limitations as well as considerations in determining the amount of detention deferral guarantee money as a result there is no legal certainty, so it is necessary to carry out ideas or ideas with the formulation of detention deferment arrangements with guaranteed money for law in the future. This type of research is a normative legal research that is research conducted with a literature study or literature study in finding data. This research is descriptive in nature which provides detailed and detailed data on existing problems. In this paper using qualitative data analysis which means to explain and conclude about the data that has been collected by the author. This research uses secondary data or scientific data that has been codified. The results of this study are to explain that the limitations in determining the amount of detention deferral guarantee money so far have not been determined, this is because there are no relevant laws and regulations governing them. So, the practice that has occurred so far is the limitation in determining the amount of the security deposit for detention based on the results of the author's research is based on the category of criminal acts, namely the severity of the crime and the amount of personal wealth of the suspect or defendant. The idea or idea that the author offers for the law in the future is to make restrictions on the amount of the detention deferment guarantee money or at least make a list of the price of the detention deferral security deposit adjusted to the category of criminal acts that is the severity or severity of the crime and the economic level of the suspect or defendant. Keywords: Formulation - Suspension of Detention - Money Guarantee